Post Traumatic Growth dalam Karya Seni Patung Abstrak - Semtu Juanto Simanjutak; Lisa Widiarti (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This research is motivated by the phenomenon of violence experienced by individuals in the early adulthood age range (18–25 years), which is often a manifestation of unresolved traumatic experiences. Unmanaged trauma can have profound psychological impacts, affecting an individual's identity, social relationships, and outlook on life. However, within the framework of positive psychology, there is the concept of Post Traumatic Growth (PTG), which explains the potential for psychological growth that can emerge after an individual experiences severe stress or trauma. PTG includes positive changes in oneself, increased meaning in life, personal strength, and appreciation for life. The concept of PTG is the main foundation in the creation of abstract sculptures that attempt to represent the psychological journey of victims of violence, from destructive conditions to recovery and self-awareness. Abstract forms are used as a visual medium to reflect inner conflict, identity fragmentation, and the complex process of internal transformation. The choice of abstraction allows for free expression of realistic forms, thus presenting a profound symbolic interpretation. The method of creation of the work is carried out through an artistic approach that emphasizes the exploration of form, texture, material, and space in three-dimensional expression. This process not only produces visual objects but also creates expressive symbols that contain narratives of psychological healing. The sculpture is presented as a contemplative medium that invites the audience to experience, understand, and interpret the inner journey of victims of violence. The resulting creation demonstrates that abstract sculpture can be a powerful means of emotional communication, facilitating public understanding of the experience of trauma and the potential for post-traumatic growth. Thus, this work not only serves as an artistic representation of the inner dynamics of victims of violence but also serves as a reflective medium that fosters awareness of the human capacity to recover and thrive after experiencing profound suffering.